2014
DOI: 10.7550/rmb.31805
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversidad de equinodermos (Echinodermata) en México

Abstract: Resumen. La posición geográfica de México lo hace uno de los países más biodiversos del planeta. El estudio de la diversidad de los equinodermos de México comenzó en el siglo XIX. En México se encuentran 643 especies de equinodermos, siendo la clase Ophiuroidea la más rica con 197 especies, Asteroidea contiene 185, Echinoidea 119, Holothuroidea 113 y Crinoidea 29. México posee algunas especies endémicas del país o de alguna región en particular. El catálogo de los equinodermos de México aún no está completo, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
14

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 3 publications
0
7
0
14
Order By: Relevance
“…Most studies on echinoderms in Mexico are taxonomic, and little information has been published on the ecology of echinoderms in this region (Solís-Marín et al, 2014). We found ophiuroids in a salinity range of 18 to 42, providing evidence that these organisms may live in brackish and even in hyperhaline environments (Salamon et al, 2012).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Most studies on echinoderms in Mexico are taxonomic, and little information has been published on the ecology of echinoderms in this region (Solís-Marín et al, 2014). We found ophiuroids in a salinity range of 18 to 42, providing evidence that these organisms may live in brackish and even in hyperhaline environments (Salamon et al, 2012).…”
Section: Discussionmentioning
confidence: 65%
“…For example, Durán-González et al (2005) reported 49 species of ophiuroids in the Gulf of Mexico, while Hernández-Herrejón et al (2008) reported 68 species, and Solís-Marín et al (2013) in the most recent review reported 79 species. In Mexico, the class Ophiuroidea represent approximately 40% (197 species) of the total species recorded (Solís-Marín et al, 2014). New records and range extensions for species of ophiuroids are often reported in the literature (Solís-Marín et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…En la zona litoral marina de Veracruz, se han descrito 116 especies de equinodermos que incluyen estrellas de mar, crinoideos, erizos, ofiuros y holoturoideos (Durán-González et al 2005, Solís-Marín et al 2014. En el caso particular del Sistema Arrecifal Veracruzano (SAV), se han reportado las especies de pepino de mar Isostichopus badionotus, Holothuria floridana, Actinopyga agassizii, Holothuria arenícola, Holothuria mexicana, Holothuria grisea, Holothuria surinamensis y Eostichopus arnesonii (Durán-González et al 2005, Solís-Marín et al 2007, las cuales son de interés comercial a nivel mundial (Purcell et al 2012).…”
Section: Introductionunclassified
“…Si bien, las citadas contribuciones científicas son importantes para las costas mexicanas del Golfo de México, se ha recomendado que es necesario generar más información sobre la abundancia y densidad de los equinodermos y su relación con ambientes bióticos y abióticos (incluyendo datos poblacionales como crecimiento, reproducción y alimentación) (Solís-Marín et al 2013) en especial en ecosistemas poco explorados (Solís-Marín et al 2014).…”
Section: Introductionunclassified